Audited quarterly accounts and earnings response coefficients - Malik, Mazrah; Fauzi Saidin, Saidatunur; Osman, Mohammad Noor Hisham (De La Salle University Publishing House, 2016)
The production of quarterly accounts has become a mandatory requirement for listed companies in many countries. However, these accounts are not required to be audited in many jurisdictions, which expose these accounts to the risk of errors and manipulations. The purpose of this study is to examine the investors’ response towards auditor’s involvement in quarterly accounts. Analysis is based on matched pair sample of 60 listed companies in Bursa Malaysia in the year 2012. The result of the OLS regression shows that the earnings response coefficients of quarterly accounts that have been audited are statistically higher than those not audited. The result provides support for the contention that investors place greater reliability on quarterly accounts that have auditor’s involvement. The finding provides support for the need of auditor’s involvement in the quarterly accounts. However, additional costs associated with auditing the quarterly accounts should also be considered.